2015
DOI: 10.1371/journal.pone.0117919
|View full text |Cite|
|
Sign up to set email alerts
|

Care Seeking Behaviour for Children with Suspected Pneumonia in Countries in Sub-Saharan Africa with High Pneumonia Mortality

Abstract: Pneumonia is the leading cause of childhood mortality in sub-Saharan Africa (SSA). Because effective antibiotic treatment exists, timely recognition of pneumonia and subsequent care seeking for treatment can prevent deaths. For six high pneumonia mortality countries in SSA we examined if children with suspected pneumonia were taken for care, and if so, from which type of care providers, using national survey data of 76530 children. We also assessed factors independently associated with care seeking from health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
83
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 41 publications
(45 reference statements)
19
83
2
Order By: Relevance
“…Our findings revealed that caretakers were 1.8 times more likely to delay consulting a health facility if their child was a female than male. Similar findings were reported in studies done in Pakistan, India and Africa [16,18,19]. Surprisingly, age of child was not found to influence health facility consultation in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed that caretakers were 1.8 times more likely to delay consulting a health facility if their child was a female than male. Similar findings were reported in studies done in Pakistan, India and Africa [16,18,19]. Surprisingly, age of child was not found to influence health facility consultation in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The finding concurs with a study conducted in the communities of Nigeria, Ethiopia and De-mocratic Republic of Congo. 34 Although there was no reported significant association to other socio-demographic characteristics such as child's gender, location, and number of symptoms dissimilar from other reports, 5,28,32,35,36 this informs the need to strengthen efforts on educating caregivers on the signs and symptoms, the severity of the ARI episodes, and on when and where to immediately take the child to the health facility. The reason for this disparity is not clear but suggests that it was probably due to the variances in methodologies (different approach in data collection, study population, cultural differences and locale of the study).…”
Section: Discussionmentioning
confidence: 76%
“…Unfortunately, only one in five caregivers in developing countries can recognize the danger signs of pneumonia like rapid breathing and chest indrawing, and only half of children under 5 with pneumonia are taken to an appropriate healthcare provider [6]. In a population based survey carried out in six countries in Sub-Saharan Africa, only about 18% and 30% of children with suspected pneumonia in Nigeria and Ethiopia, respectively, were taken to hospital for healthcare [7]. In a systematic review of ninety-one studies that reported recognition and/or care seeking for diarrhoea, pneumonia, and malaria in low and middle income countries (LMICs), it was shown that the median sensitivity of recognition of pneumonia among caregivers was low (45.8%) and care seeking from community health worker for pneumonia was 4.2% [8].…”
Section: Introductionmentioning
confidence: 99%